THE CRUCIAL ROLE OF THE INFORMATION SYSTEM (CIPEEX, 2025)
Digital transformation has become essential for organizational competitiveness, presenting both challenges and opportunities. This study examines the impact of this transformation, highlighting how information systems play a central role in the evolution of business models. More than just the digitization of processes, digital transformation requires a comprehensive strategic shift aimed at improving operational efficiency through automation, increasing agility and innovation, and providing a personalized and interactive customer experience. However, for this change to be successful, effective change management strategies must be adopted due to challenges such as technological integration, resistance to innovation, lack of specific skills, and concerns about data security and privacy. Additionally, digital transformation is not limited to the adoption of new tools; it requires a cultural shift that prepares employees to face new scenarios. Organizations must follow a structured approach, plan strategically, assess emerging trends, and review their current processes. Companies that overcome these obstacles will be better positioned to enhance their efficiency, deliver personalized customer experiences, and explore innovative new business models.
Keywords: digital transformation; information systems; automation; business models